Modeling the effect of hypoxia and DNA repair inhibition on cell survival photon irradiation - Liew, Hans; Klein, Carmen; Zenke, Frank T.; Abdollahi, Amir; Debus, Jürgen; Dokić, Ivana; Mairani, Andrea (International journal of molecular sciences, 2019)
Mechanistic approaches to modeling the effects of ionizing radiation on cells are on the rise, promising a better understanding of predictions and higher flexibility concerning conditions to be accounted for. In this work we modified and extended a previously published mechanistic model of cell survival after photon irradiation under hypoxia to account for radiosensitization caused by deficiency or inhibition of DNA damage repair enzymes. The model is shown to be capable of describing the survival data of cells with DNA damage repair deficiency, both under norm- and hypoxia. We find that our parameterization of radiosensitization is invariant under change of oxygen status, indicating that the relevant parameters for both mechanisms can be obtained independently and introduced freely to the model to predict their combined effect.